Emancipation of and by Computer Supported Cooperative Work - Hellman, Riitta (DAIMI Report Series, 1988)
Computer supported cooperative work (CSCW) currently arouses plenty of interest. There is, anyhow, an evident tendency to regard CSCW-technologies (e.g. electronic mail, hyperdocument applications, calendar systems, and the like) as belonging to the office territory. This paper aims at illustrating some possibilities of utilizing CSCW-applications in an industrial setting (inventory management system). In other words, it is daimed that CSCW-technologies are relevant consequences of the use of these technologies. I also discuss how to avoid the creation of unnecessary applicational complexity in the case of employing CSCW-technologies.